Generalized minimum variance control for buildings under seismic ground motion. - Guenfaf, L. (Earthquake engineering & structural dynamics.)
The generalized minimum variance (GMV) algorithm for the control of civil engineering structures is developed and presented in this paper. This algorithm needs the knowledge of the seismic excitation model to derive the autoregressive moving average exogen model of the structure. Then the GMV control is applied. The control is designed such that the variance of the generalized cost function is minimized. To demonstrate the effectiveness of this control technique, simulation tests using a single degree of freedom structure are performed. The results show that the relative displacement of the structure and the control effort are significantly reduced.